Linear Elastic Numerical Modelling For Failure Prediction - An Assesment - Synopsis (53d33219-d247-4a4b-8257-b37f5085f7fc) - S. K. Murphy (The Southern African Institute of Mining and Metallurgy, 2012)
A partial shaft pillar extraction project was embarked on at a mine in the West Wits mining region in South Africa. Prior to the extraction, a rock engineering assessment was conducted with the main objective being to establish which areas of the shaft pillar could be extracted without unduly affecting the stability of major infrastructure within the shaft pillar. Standard numerical modelling methods were used to conduct this assessment and several areas were identified for extraction. However, during the extraction process, it was found that the infrastructure was affected more than was originally predicted by linear elastic modelling. In addition to this, several large events resulted in far more large aftershocks than would normally be predicted. In order to gain an understanding of this phenomenon, seismic data was integrated with numerical modelling as follows: > The seismic data in the form of displacements was integrated in 3D space within the model to assess the effect of static stress changes associated with seismic activity > Data from large events was integrated onto specific structures, where displacements associated with large events were integrated onto the plane of structure in question. This paper describes the methodology and results obtained from each of the above processes and include insights into the mining process that were previously unfathomable using standard linear elastic numerical modelling. The way forward for this rock engineering assessment of partial shaft pillar extraction is also discussed.